GENESIS OF PONJONG PINK LIMESTONE, GUNUNGKIDUL, SPECIAL REGION OF YOGYAKARTA – INDONESIA (GENESA BATUGAMPING MERAH MUDA PONJONG, GUNUNGKIDUL, DAERAH ISTIMEWA YOGYAKARTA - INDONESIA) - Anastasia Dewi Titisari, Anastasia Dewi Titisari (Departmen Teknik Geologi, 2015)
The Ponjong pink limestone is located in the Gunungkidul Regency, approximately 60 km southeast of Yogyakarta. The rock belongs to member of Wonosari-Punung Formation of Southern Mountains. The mineralogical and geochemical characteristics of the pink limestone provide an important background to understanding the origin of the rock. The petrographical observation and X-ray diffraction results indicate that the pink limestone is characterized by calcite, algae, foraminifera and very small amount of siderite and titanite. Major element analysis of the rock shows an anomalous high content of Fe 2O3 (0.51 wt. %) and TiO2 (0.04 wt. %). In comparison, the white-grey limestone from the same area of the pink limestone, contains very low Fe 2O3 (0.10 wt. %) and TiO2 (0.01 wt. %). The reasonably higher content of Fe 2O3 and TiO 2 in the pink limestone may correspond to the enrichment of the compounds in the rock. The enrichment could be occur syn and/or post deposition of the Wonosari-Punung limestone. Source of the Fe2O3 and TiO 2 may derived from terrigenous particles of Nglanggran Formation as this formation is typified by relatively high contents of Fe2O3 (5.26-6.92 wt. %), TiO 2 (0.67-0.87 wt.%) and SiO 2 (56.5-65.3% wt.%). Fe 2+ of the Fe 2O3 might partially replace Ca 2+ of calcite (CaCO 3), formed siderite (FeCO3), as siderite is isomorphs with calcite. Probably, titanite (CaTiOSiO4) was a result of reaction of the limestone and the terrigenous materials. The siderite and titanite are typically pinkish red to yellowish brown in color and are therefore interpreted to be responsible in giving pink color of the limestone.